Expression of MRP8/MRP14mRNAin Monocytes of Periodontitis: Comparison between Diabetic and Non Diabetic Patients - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
The severity of periodontitis on patients with type 2 Diabetes Mellitus patients was strongly thought caused by decreasing of leukocytes function such as monoctyes and neutrophils. In our previous research it was found that calprotectin (MRP8/MRP14) level in leukocytes of periodontitis patients with type 2 DMwas higher than periodontitis in non DM.The aim of this study was to determine calprotectin (MRP8/MRP14) mRNAexpression in human monocytes of periodontitis patients with type 2DMand without DM.Monocytes were isolated from the peripheral blood of periodontitis patients with uncontrolled type 2 DM,controlled type 2 DM,and non DM.The expression of total RNAcalprotectin (MRP8and MRP14)were detected by RTPCRusing GAPDHas the innate control. It was observed that the value of MRP8/MRP14mRNAexpression DMpatients were higher than non DM,and the highly significant increase expression (p